1997
DOI: 10.1038/sj.leu.2400744
|View full text |Cite
|
Sign up to set email alerts
|

Does transmembrane communication through gap junctions enable stem cells to overcome stromal inhibition?

Abstract: ronectin on stromal cells. 11 Lipophilic compounds that do not affect GJIC had no effect onWe asked if the gap junctions which are present in haemo- drugs (Ref. 13 and Krenács and Rosendaal, in preparation).Keywords: blood formation; haemopoietic regulation; gap junctions; Cx43; Amphotericin B; stem cells; stroma Gap junctions are intramembranous channels through the walls of adjacent cells which permit the passage of watersoluble molecules smaller than 1 kDa, which could be messengers. Channels are gated, op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 7 publications
(6 reference statements)
1
20
0
Order By: Relevance
“…Moreover, using radiation chimeras, the authors showed that impaired T-and B-lymphocyte maturation was due to a defect in the stromal cells of both the thymus and BM. This confirms Rosendaal hypothesis 11,15,18 that Cx43 expression in the stroma is critical during early growth and regeneration of the hematopoietic system, but not for maintenance of the steady-state blood cell production.…”
Section: Introductionsupporting
confidence: 75%
See 1 more Smart Citation
“…Moreover, using radiation chimeras, the authors showed that impaired T-and B-lymphocyte maturation was due to a defect in the stromal cells of both the thymus and BM. This confirms Rosendaal hypothesis 11,15,18 that Cx43 expression in the stroma is critical during early growth and regeneration of the hematopoietic system, but not for maintenance of the steady-state blood cell production.…”
Section: Introductionsupporting
confidence: 75%
“…18 In contrast, using a direct assay, we have shown that GJs are actually involved in the maintenance of quiescence. We also suggest that such regulation can be achieved through signaling for asymmetric cell division.…”
Section: Discussionmentioning
confidence: 92%
“…17 We compared blood formation by WT and KO stems as published. 1 An intracellular injection of lucifer yellow 18 into WT stroma spread over 4 to 5 cell diameters but did not pass from one KO cell to another. KO cells passed neurobiotin to the next cell but no further.…”
Section: Competitive Repopulationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] Gap junctions have been comprehensively reviewed. 13 In 1995 and 1997, we proposed 1,14 that Cx43 gap junctions between stromal and hematopoietic cells determine hematopoiesis. If this were the case, was this effect because of coupling between hematopoietic and stromal cells or between stromal cells alone?…”
Section: Introductionmentioning
confidence: 99%
“…Current knowledge is however sparse. It has been proposed that Cx32, Cx43 and GJIC play a role in HSC maintenance and differentiation (Hirabayashi et al, 2007b;Ploemacher et al, 2000;Rosendaal et al, 1997). Indeed, Cx32 knockout mice exhibit more undifferentiated HSC and fewer progenitor cells, suggesting a role of Cx32 in maturation of HSC to progenitor cells (Hirabayashi et al, 2007a;Hirabayashi et al, 2007b).…”
Section: Somatic Stem Cellsmentioning
confidence: 99%